Pelanggaran Hak Asasi Manusia Perempuan Dan Tanggung Jawab Negara - Vrenses Batuwael; Irma Halima Hanafia; Wilshen Leatemia (PATTIMURA Law Study Review, 2023)
ABSTRACT: Human rights and freedoms, especially women are limited, as well as discrimination against women in the Taliban, Afghanistan. In this case women are prohibited from being active in all fields, even to get education is also prohibited by the state. In fact, women were encouraged to leave government, in addition women are also prohibited from traveling to public places without being accompanied by a man, must cover themselves in public places and other things that aim to limit women's rights. The research method used in analyzing and discussing problems is normative. This research is focused with the aim of analyzing the non-fulfillment of women's human rights as a result of discrimination that can be qualified as a human rights violation, as well as the state's responsibility in fulfilling women's human rights whose rights are violated. The results of the study state that violations of women's human rights in Afghanistan due to discrimination can be said to be human rights violations because they violate the basic principles of the Universal Declaration of Human Rights and CEDAW. In terms of the Taliban abusing their power by making policies without respecting women's human rights. Afghanistan is trying to protect the fulfillment of women's human rights whose rights have been violated, by ratifying CEDAW, forming a political mission with the United Nations, namely UNAMA, forming the EVAW Law, and working with international organizations such as UNIFEM, then replaced by UN Women. And if the state cannot deal with violations of women's human rights, as well as provide justice. So the prosecution of human rights violators is part of the jurisdiction of the International Criminal Court through the security council acting under Chapter VII of the UN Charter.